Cosmological simulations of the circumgalactic medium with 1 kpc resolution: enhanced H i column densities - Voort, Freeke van de; Springel, Volker; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society. Letters, 2019)
ABSTRACT. The circumgalactic medium (CGM), i.e. the gaseous haloes around galaxies, is both the reservoir of gas that fuels galaxy growth and the repository of